Environmental impact of brine disposal of desalination plants - Sim, Genevieve Jia Li. (2011)
This study aims to develop an improved LCIA method to be used for the evaluation of ecotoxicity impacts of brine disposal from the seawater desalination process. Oceanic brine disposal has environmental impacts that are evident in many parts of the world, however, quantification assessment studies on this subject is limited due to the restrictions of current LCIA approaches. With the improved method, the eco-toxicity potential (ETP) impacts of brine disposal are better quantified as it takes certain brine constituents that were previously ignored or had its effects downplayed into consideration. The evaluation was done in three steps: a) Develop the new LCIA approach b) Categorise the key brine constituents into groups c) Determine the Characterisation Factor of each group and calculate the final ETP score. From the results derived, the ETP Characterization Score differed greatly from the values published in other studies. It is concluded that salinity, which had a large influence on the ETP Characterization Score, is the most influential constituent of brine. Thus, the impact of salinity should not be underestimated.